Letters as Weapons: The edition of books in favor of the Franco's regime in Buenos Aires during the Spanish Civil War (1936-1939) (Estudios de Historia de España, 2019)
In the context of the Spanish Civil War (1936-1939), books became key elements of popularization and were used by both sides in order to promote accessions and disqualifythe enemy in the context of the struggle. In this work, we will try to reconstruct a catalog of those books that were published in the city of Buenos Aires during the course of the war in Spain and the immediate civil postwar, in which a clear adherence to the principles of the military uprising in the peninsula first and the Franco regime later. We will try to identify the editorial spaces that were behind these publications, the most outstanding authors and the main contents that were developed in these works.
Keywords: Spanish Civil War; Propaganda; Books; Franco; Buenos Aires